La (re)construcció visual i retòrica de Jaume I a la Festa de l'Estendard de Mallorca durant l'època foral. - SALES, FRANCESC GRANELL (Scripta, 2017)
This paper attempts to discuss the manner in which the image of king James I was customized and established in the Festa de l'Estendard, the annual commemoration ceremony of the christian conquest of the city of Mallorca. We will do so through an analysis of the visual and rhetorical elements planned for the unfolding of the ritual. One should focus particular attention on two of these elements: the standard bearer on horseback well attired in armour and other objects and the speech known as the «Sermó de la Conquesta» delivered by a cleric.